Methods used for extraction of plant volatiles have potential to preserve truffle aroma: A review. Issue 2 (18th February 2022) - Phong, Win Nee; Gibberd, Mark R.; Payne, Alan D.; Dykes, Gary A.; Coorey, Ranil
Abstract: Truffles are considered one of the world's most highly prized foods mainly due to their desirable organoleptic properties and rarity. However, truffles are seasonal (harvested mostly in winter from June to August in the Southern Hemisphere and from December to February in the Northern Hemisphere) and extremely perishable. Truffles deteriorate rapidly showing undesirable changes within 10 days from harvest in aroma and visual appearance after harvest. The very short postharvest shelf life (about 7–10 days) limits the potential for export and domestic consumption all year round. Several preservation methods have been studied to prolong their shelf life without the loss of aroma. However, all traditional preservation techniques have their own shortcomings and remain challenging. The extraction of natural truffle aroma volatiles for food applications could be a potential alternative to replace the existing synthetic flavoring used for processed truffle products. Four commonly used extraction methods for recovering volatile compounds from plants, namely, supercritical carbon dioxide extraction, Soxhlet extraction, distillation, and cold pressing, are critically analyzed. Up to date, existing research about the extraction of aroma volatiles from truffles is limited in the literature but based on the volatility of the key truffle volatile compounds, supercritical carbon dioxide extraction may offer the best possibility so that a natural truffle‐based product that can be used in food applications throughout the year can be made available.